Pengaruh Proses Pengembangan dan Revisi Formularium Rumah Sakit terhadap Pengadaan dan Stok Obat - YUSI ANGGRIANI; DWI PUDJANINGSIH; DWI SURYAWATI (JURNAL ILMU KEFARMASIAN INDONESIA, 2008)
Appropriate selection of medicines is needed to support its rational use. Medicines selection based upon a hospital formulary is an attempt to uncreate the medicine efficiency management. The objective of this study Was to evaluate and compare the intrinsic value of seven grade C-hospital formularies in Yogyakarta, also concerning the development and revision of the used fonnularies. The result showed that the percentage of purchase of non-formularium medicines and that of the non-formularium medicines in stock were influenced by the frequency of revision of the formulary itselfand drug policy in relation to the addition and deletion process of the used fonnulary. Non-formulary medicines purchase was low in hospitals which frequently revised the formulary, but hospital With no policy concerning addition and deletion increased the purchase of non formulary medicines. Besides that the use of brand name products in hospitals of the state was much lesser than that used in non-state hospitals (296-532 vs 573-1575). Fonnulary evaluation of state hospitals in comparison with non-state hospitals Were as follows: essential medicines (41-71% vs 20-28%), medicines with primary literature (73-90% vs 67-73%), drugs with single component (41-71% vs 20-28%) The quality of formulary in state and non-state grade C-hospitals in Yogyakarta must be improved.